Characterization of clay material and rice husk from northeast Colombia (2021)
This research was to study materials from the region to use them industrially applying the circular economy concept. Clay Material and Rice Husk were evaluated in the manufacture of ceramic products. X-ray Diffraction and X-ray Fluorescence techniques were used to determine the raw materials' chemical and mineralogical composition. Thermal analysis techniques (TG and DTG) were used to complement the study. The XRD results showed an abundance of quartz. The results of the thermal analysis establish significant losses due to calcination. The thermal conductivity was also measured in ceramic specimens made from two types of pastes, one with 100% Clay Material and the other with a 5% substitution for Rice Husk. The results showed a decrease in thermal conductivity in the test tubes with the addition of Rice Husk. Consequently, the Rice Husk as a substitute for the Clay Material allows for ceramic production with thermal efficiency.